(untitled) (Global Journal of Human-Social Science, 2016)
Northern Nigeria among other regions of the country has witnessed various degrees of insecurity with its resultant effect on the Internally Displaced Persons (IDPs), economic fortunes of the affected communities and overall standard of living of those living within the affected states. This has made security the major concern for Nigerian government and has invested huge resources to that effect. Insecurity in the north has not only prevented development of that region but also hinders foreign investment, disrupt social activities, peaceful coexistence and has become a great threat to the growth and development of the region in particular and Nigeria in general. This paper therefore, examined the insecurity situation in the Northern Nigeria and its effects on the IDPs.